Alternative Historiographies of the Digital Humanities - Koh, Adeline; Kim, Dorothy (Book collections on Project MUSE., 2021)
In Silencing the Past: Power and the Production of History, Michel-Rolph Trouillot writes that by examining the process of history we can “discover the differential exercise of power that makes some narratives possible and silences others." Alternative Historiographies of the Digital Humanities examines the process of history in the narrative of the digital humanities and deconstructs its history as a straight line from the beginnings of humanities computing. By discussing alternatives histories of the digital humanities that address queer gaming, feminist game studies praxis, Cold War military-industrial complex computation, the creation of the environmental humanities, monolingual discontent in DH, the hidden history of DH in English studies, radical media praxis, cultural studies and DH, Indigenous futurities, Pacific Rim postcolonial DH, the issue of scale and DH, the radical, Indigenous, feminist histories of the digital database, and the possibilities for an antifascist DH, this collection hopes to re-set discussions of the DH straight, white origin myths. Thus, this collection hopes to reexamine the silences in such a straight and white masculinist history and how power comes into play to shape this straight, white DH narrative.